Efficacy of Neem Oil on Cardamom Thrips, Sciothrips cardamomi Ramk., and Organoleptic Studies. (13th March 2014) - Stanley, Johnson; Preetha, G.; Chandrasekaran, S.; Gunasekaran, K.; Kuttalam, S.
Abstract : The neem tree contains promising pest control substances which are effective against many pests. Oil extracted from neem seeds was used against cardamom thrips, Sciothrips cardamomi, a severe and economic pest of cardamom. Neem oil formulations, namely, Tamil Nadu Agricultural univeristy neem oil (TNAU NO) (acetic acid & citric acid), were found effective against the pest with a overall damage reduction of 30% after 14 days of treatment. The percent damage reduction in capsules over control after three consecutive sprays of TNAU NO(C) 2% and TNAU NO(A) 2% was 78.3 and 75.2 percent, respectively. The newly extracted and unformulated neem oil, though found inferior to the formulated one, still found to cause 50% and 70% reduction in damage caused by thrips at two and three rounds of sprays, making it useful in pest management. Organoleptic tests conducted on cardamom capsules sprayed with neem oil revealed no significant difference in taste, aroma, and overall acceptability of cow milk boiled with cardamom. Thus, TNAU NO (A and C) 2% was found effective against cardamom thrips with no adverse organoleptic properties and can be recommended.